2015
DOI: 10.1093/jamia/ocv078
|View full text |Cite
|
Sign up to set email alerts
|

Engaging adolescents in a computer-based weight management program: avatars and virtual coaches could help

Abstract: This study provides evidence supporting the use of avatars and virtual agents, designed using participatory approaches, to be included in the continuum of care. Increased probability of engagement and long-term retention of overweight, obese adolescent users and suggests expanding current chronic care models toward more comprehensive, socio-technical representations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 27 publications
(31 reference statements)
2
66
0
Order By: Relevance
“…Current findings also contribute to growing body of literature on adopting virtual agents in the context of health promotion for children and adolescents (Ahn et al, 2015;Ahn et al, 2016;LeRouge, Dickhut, Lisetti, Sangameswaran, & Malasanos, 2016;Wang et al, 2015) by suggesting that virtual agents may foster relatedness perceptions in children, particularly when the virtual agents deliver external rewards. Earlier research indicates that children perceive relationships and friendships differently than adults because their judgment of people remains relatively underdeveloped and self-centered until their cognitive abilities mature in adolescence (Bigelow & LaGaipa, 1980).…”
Section: Discussionsupporting
confidence: 56%
“…Current findings also contribute to growing body of literature on adopting virtual agents in the context of health promotion for children and adolescents (Ahn et al, 2015;Ahn et al, 2016;LeRouge, Dickhut, Lisetti, Sangameswaran, & Malasanos, 2016;Wang et al, 2015) by suggesting that virtual agents may foster relatedness perceptions in children, particularly when the virtual agents deliver external rewards. Earlier research indicates that children perceive relationships and friendships differently than adults because their judgment of people remains relatively underdeveloped and self-centered until their cognitive abilities mature in adolescence (Bigelow & LaGaipa, 1980).…”
Section: Discussionsupporting
confidence: 56%
“…More product development and research focused on non-adult populations, including children, teens, and older adults, is needed. Children and teenagers may be particularly interested in the use of VR and AR technology as a form of entertainment and may be more receptive to nutrition education and behavior change approaches which incorporate this technology [18,19]. Previous research has found that teenagers were interested in a VR avatar approach to weight loss because it would fit with their lifestyle and help support healthy behaviors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Children and teenagers may be particularly interested in the use of VR and AR technology as a form of entertainment and may be more receptive to nutrition education and behavior change approaches which incorporate this technology [18,19]. Previous research has found that teenagers were interested in a VR avatar approach to weight loss because it would fit with their lifestyle and help support healthy behaviors [19]. The use of VR and AR may also be a desirable and effective approach for nutrition education and behavior change for older adults who have mobility limitations or limited access to in-person nutrition education programs [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the use of virtual agents in health care has been explored in different domains, spanning from nursing (Bickmore et al, 2012 ) and counseling (LeRouge et al, 2015 ) to training of people with autism (Burke et al, 2018 ) and assistance to elderly and cognitively impaired people (Yaghoubzadeh et al, 2013 ; Chauveau et al, 2018 ). Virtual agents can be implemented on different devices in an non intrusive way, thus guaranteeing portability and continuity in therapies, and can be personalized to meet the needs of specific patients or groups of patients.…”
Section: Modeling Story Characters With the Mea Agentmentioning
confidence: 99%